The Strategies Of English Pragmatic Competence Of Pre-School Aged Children - Nur Arifah Drajati (Bandar Lampung University (UBL), 2013)
Pre-school aged children employ certain strategies in order to acquire language, including pragmatic competence in English of pre-school aged children. The studies are to investigate the learning strategies to acquire pragmatic competence in English of pre-school aged children and to investigate the communication strategies to acquire pragmatic competence in English of pre-school aged children.The research employs a qualitative approach with sectional design. The data are spoken speeches gathered from observation of 4 children of 4, 5, 6, and 7 years old. The collected data are analyzed by using performance analysis technique. The analysis is based on linguistic behaviors and actual speeches performed by the subjects as reflection of their pragmatic competence and strategies to acquire it.The analysis of the data came up with the following finding. The learning strategies to acquire pragmatic competence consist of cognitive strategies and social strategies. The cognitive strategies contain four types: imitating speeches, repeating strategies, revising speeches and translating in the form of translation from Indonesian into English. The social strategies consist of two types requesting clarification and asking for inter-responses.Second, the communication strategies to acquire pragmatic competence of pre-school aged children consist of two categories:non-verbal form and verbal form. The non verbalform include the use of pictures and songs and strategies of expressing speech contents.The findings contribute to the development of the theory of language acquisition strategies, particularly the theories of learning strategies and communication strategies. Practically, the findings of the study can broaden the educator’s knowledge of strategies in acquiring pragmatic competence of child learners.